Preparation method of CoZr-NF monolithic catalyst for catalytic oxidation of o-xylene
By doping cobalt oxide and zirconium oxide in nickel foam, the CoZr-NF monolithic catalyst is prepared, which solves the problems of low catalytic efficiency and easy blockage of powdered catalysts, and achieves efficient catalytic oxidation and degradation effects.
Patent Information
- Application Number
- CN202411662408.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-20
- Publication Date
- 2025-02-25
AI Technical Summary
In the prior art, powdered catalysts are used to perform catalytic oxidation of orthoxylene, which has low catalytic efficiency, can easily clog the reactor and is not easy to recover.
Using CoZr-NF monolithic catalyst, a highly efficient monolithic catalyst is prepared by doping cobalt oxide and zirconium oxide in nickel foam and using ultrasonic atomization and decomposition method.
The conversion rate of orthoxylene is achieved at least 90% within the reaction temperature range below 210°C, with good catalytic activity and stability, and avoiding the problems of reactor clogging and catalyst recovery.
Smart Images

Figure CN119500140A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of catalytic oxidation degradation of VOCs, and in particular to a method for preparing a CoZr-NF integral catalyst for catalytic oxidation of o-xylene. Background Art
[0002] Volatile organic compounds (VOCs) mainly come from coal and petrochemical industries, fuel and paint manufacturing, textile printing and other processes. They are potentially harmful to the environment and human health. The control and treatment of VOCs is very important, and end-of-pipe treatment technology needs to be further developed. Ortho-xylene is the main characteristic pollutant of waste gas from the petrochemical industry and petroleum refining waste gas, and is also the main controlled pollutant of ozone and PM2.5. Long-term or high-concentration exposure to it has carcinogenic potential to humans, and it is urgent to treat it.
[0003] Due to its advantages of low energy consumption, strong processing capacity and no secondary pollution, catalytic oxidation is one of the effective ways to control the emission of volatile organic pollutants, and the core of this method lies in the design of efficient catalysts. Transition metal oxide catalysts have greater cost advantages than precious metal catalysts, and have rich structural adjustments, simple preparation methods, high reproducibility and high structural stability. Transition metal cobalt (Co) and its oxides, which belong to Group VIII with precious metals and have similar electronic structures and multiple variable valence states, even show catalytic combustion performance superior to that of precious metals in the catalytic combustion of alkanes, esters, etc., and can significantly reduce the cost of catalytic combustion catalysts, which is of great significance for the promotion of catalytic combustion technology and the realization of deep purification and treatment of VOCs.
[0004] Conventional catalytic oxidation catalysts are all powder catalysts, which have the disadvantages of poor mechanical properties, low catalytic efficiency, large pressure drop and easy reactor clogging. Monolithic catalysts have the advantages of low bed pressure, good heat and mass transfer, simple industrial scale-up and easy recycling and regeneration. By replacing powder catalysts, they can be better applied to industrial production.
[0005] The three-dimensional interconnected nickel foam (NF) scaffold has the advantages of high porosity, good stability, good thermal stability, strong mass transfer capacity and low cost. It is considered to be a new type of catalyst carrier and is widely used in many industrial fields. Chinese invention patent CN115608368A discloses a monolithic catalyst with high activity and low cost. The patent successfully grows CeO2 on the surface of the foam carrier Co-Ni by in-situ growth. The catalyst has a good effect on the degradation of butyl acetate. 100 The temperature can reach 230℃. This preparation method greatly improves the activity and stability of the monolithic catalyst, while also solving the problem of low adhesion of the active components of the monolithic catalyst. SCatalytic degradation is also a very feasible and efficient means. Summary of the invention
[0006] The problem in the prior art is that the powdered catalyst is used to catalytically oxidize o-xylene, the catalyst has low catalytic efficiency, is easy to clog the reactor, and is difficult to recover. In view of the above technical problems, the present invention provides a method for preparing a CoZr-NF monolithic catalyst for catalytic oxidation of o-xylene, which comprises the following preparation steps:
[0007] NF is placed in a quartz tube, and the quartz tube is heated to 200°C and kept at a constant temperature for 2-3 hours. Then, the quartz tube is heated to 550°C and kept at a constant temperature for 2-3 hours. After the reaction is completed, the CoZr-NF monolithic catalyst is obtained.
[0008] When the temperature of the quartz tube is raised to 200°C, the carrier gas passes all the reactive aerosol from one end of the quartz tube and is discharged from the other end of the quartz tube. The reactive aerosol is obtained by atomizing a soluble salt solution of an active metal element.
[0009] The NF is circular in shape, and the diameter of the NF is exactly equal to the inner diameter of the quartz tube. The NF is placed in the quartz tube in a manner of being tangential to the inner wall of the quartz tube to seal the quartz tube.
[0010] Preferably, the carrier gas is nitrogen or an inert gas.
[0011] Preferably, the active metal elements include Co and Zr.
[0012] Preferably, the molar ratio of Zr to Co in the active metal elements is 0.1-1:1, and the molar ratio of Co to NF is 0.05-0.25:1.
[0013] Preferably, the NF is pretreated NF, and the pretreatment method comprises the following steps:
[0014] The NF was ultrasonically cleaned with deionized water, hydrochloric acid, and anhydrous ethanol for at least 10 min, and then vacuum dried. Finally, it was calcined at 600 °C for 3 h.
[0015] Preferably, the concentration of hydrochloric acid is 3-5 mg / mL.
[0016] Preferably, the average pore size of the NF is 110 PPI.
[0017] The present invention has the following beneficial effects:
[0018] The present invention successfully doped cobalt oxide and zirconium oxide into nickel foam through ultrasonic atomization decomposition method to obtain an integral catalytic oxidant. The integral catalytic oxidant has good catalytic activity and stability, can achieve at least 90% conversion rate of o-xylene within a reaction temperature range below 210°C, and has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] Figure 1 : It is a schematic diagram of the reaction device adopted in the present invention.
[0020] Figure 2 : is the SEM image of the CoZr-NF monolithic catalyst obtained in Example 1.
[0021] Figure 3 : is the TEM image of the CoZr-NF monolithic catalyst obtained in Example 1.
[0022] Figure 4 : is the XRD pattern of the CoZr-NF monolithic catalyst obtained in Example 1.
[0023] Figure 5 : is a graph showing the change in the conversion rate of o-xylene over time during the catalytic oxidation degradation of o-xylene by the CoZr-NF integral catalyst obtained in Example 1 at 203°C.
[0024] Figure 6 : The conversion rate of o-xylene obtained by the CoZr-NF monolithic catalyst obtained in Example 1 after four catalytic oxidation temperature gradient tests as a function of temperature DETAILED DESCRIPTION
[0025] The present invention is described in detail below with reference to the examples. However, it should be understood that the following examples are only illustrative of the embodiments of the present invention, and are not intended to limit the scope of the present invention.
[0026] The length of the quartz tube in the following examples of the present invention is 37 cm.
[0027] The reaction apparatus used in the following embodiments of the present invention is as shown in the attached specification. Figure 1 As shown. The mouth of the glass flat-mouth bottle is connected to the nitrogen bottle and the quartz tube through different connecting tubes respectively. The bottom of the glass flat-mouth bottle contains a soluble salt solution of active metal elements. The soluble salt solution of active metal elements is immersed in an ultrasonic atomizer, and the ultrasonic atomizer is connected to an external switch through a wire to start. The connecting tube between the quartz tube and the glass flat-mouth bottle is made of Teflon, and an insulation tube is also provided on the outer surface of the connecting tube. The glass flat-mouth bottle is kept at a constant temperature in a water bath at 25°C. The soluble salt solution of active metal elements is obtained by uniformly dispersing cobalt nitrate and zirconium nitrate in 50mL of deionized water.
[0028] The NF used in the following embodiments of the present invention is a pre-treated NF, and the pre-treatment method is as follows:
[0029] The NF was ultrasonically cleaned with deionized water, hydrochloric acid, and anhydrous ethanol for 10 min respectively, and then vacuum dried. Finally, it was placed at 600°C for high temperature calcination for 3 h. The NF was purchased from Kunshan Guangjiayuan Electronic Materials Business Department, and the item number is GJYNI320110. The average pore size of the NF is 110 PPI. The model is 200mm*300mm*1.5.
[0030] Example 1
[0031] A method for preparing a CoZr-NF monolithic catalyst for catalytic oxidation of o-xylene, the preparation steps of which are as follows:
[0032] 1 g of NF was placed in a quartz tube of a reaction device, and the quartz tube (effective heating length was 20 cm) was heated to 200°C in a tubular resistance furnace and kept at this temperature for 3 h. The quartz tube was then heated to 550°C and kept at this temperature for 3 h. After the reaction was completed, a CoZr-NF monolithic catalyst was obtained.
[0033] When the temperature of the quartz tube began to rise to 200°C, nitrogen gas was introduced into the glass bottle from one end of the quartz tube at a flow rate of 0.8 L / min and discharged from the other end.
[0034] The reactive aerosol is an aerosol obtained by atomizing a soluble salt solution of an active metal element;
[0035] The molar ratio of zirconium element to cobalt element in the soluble salt solution of active metal elements is 0.5:1;
[0036] The molar ratio of cobalt element to NF in the soluble salt solution of active metal element is 0.15:1;
[0037] The NF is circular in shape and 1.5 cm thick. The diameter of the NF is exactly equal to the inner diameter of the quartz tube of 9 mm. The NF is placed in the quartz tube in a tangential manner to the inner wall of the quartz tube to seal the quartz tube.
[0038] The SEM image of the CoZr-NF monolithic catalyst obtained in Example 1 is shown in the attached specification. Figure 2 Results analysis: On the CoZr-NF catalyst, it can be observed that the broken nickel foam surface is loaded with a large number of rough and smooth spherical particle structures of different sizes. These spherical particle structures have good dispersion and may effectively increase the specific surface area of the sample, which is beneficial to improve the performance of the sample in terms of adsorption and catalysis.
[0039] The TEM image of the CoZr-NF monolithic catalyst obtained in Example 1 is shown in the attached specification. Figure 3 Results: The CoZr-NF catalyst exhibits several lattice fringes with different spacings. Among them, the lattice fringes with spacings of 0.241nm and 0.148nm correspond to the (101) and (104) crystal planes of NiO2, the lattice fringes with spacings of 0.286nm and 0.137nm correspond to the (220) and (531) crystal planes of Co3O4, and the lattice fringes with spacings of 0.296nm correspond to the (111) crystal plane of ZrO2.
[0040] The XRD pattern of the CoZr-NF monolithic catalyst obtained in Example 1 is shown in the attached specification. Figure 4 Results: The CoZr-NF catalyst showed characteristic peaks at 44.6°, 52.0° and 76.4°, which were attributed to the (111), (200) and (220) crystal planes of Ni. The characteristic peaks at 31.3°, 59.4° and 68.6°, which were attributed to the (220), (511) and (531) crystal planes of Co3O4, were shown. The characteristic peak at 30.2°, which was attributed to the (111) crystal plane of ZrO2, was shown. This indicated that the phase components of the catalyst contained Co3O4 and ZrO2 in addition to the substrate Ni.
[0041] The change of the conversion rate of o-xylene over time during the catalytic oxidation degradation of o-xylene by the CoZr-NF monolithic catalyst obtained in Example 1 at 203°C is shown in the attached specification. Figure 5 Results: The o-xylene conversion rate of CoZr-NF catalyst at 203°C was basically maintained at 90% within 20 hours, and the stability was good. Reaction conditions: catalyst mass: 1g, o-xylene concentration: 310ppm, space velocity: 10800mL / (gh); gas flow rate: 180mL / min, oxygen concentration: 20%, equilibrium time: 1h.
[0042] The conversion rate of o-xylene obtained by the CoZr-NF monolithic catalyst obtained in Example 1 after four catalytic oxidation temperature gradient tests is a graph showing the change of the conversion rate of o-xylene with temperature. Each catalytic oxidation temperature gradient test is to test the conversion rate of o-xylene of the CoZr-NF monolithic catalyst obtained in Example 1 at 160°C, 170°C, 180°C, 190°C, 200°C, 210°C, 220°C, and 230°C, respectively, and the test conditions at each temperature are exactly the same. Result analysis: In the four active cycle experiments of the CoZr-NF catalyst in the temperature range of 160-230°C, the conversion rate of o-xylene can be increased from 11% to 100%, and the stability is good. Reaction conditions: catalyst mass: 1g, o-xylene concentration: 310ppm, space velocity: 10800mL / (gh), gas flow rate: 180mL / min, oxygen concentration: 20%, equilibrium time: 1h.
[0043] Example 2 is the same as Example 1, except that the molar ratio of zirconium element to cobalt element in Example 2 is 0.1:1.
[0044] Example 3 is the same as Example 1, except that the molar ratio of zirconium element to cobalt element in Example 3 is 0.25:1.
[0045] Example 4 is the same as Example 1, except that the molar ratio of zirconium element to cobalt element in Example 4 is 0.75:1.
[0046] Example 5 is the same as Example 1, except that the molar ratio of zirconium element to cobalt element in Example 5 is 1:1.
[0047] Example 6 is the same as Example 1, except that no cobalt nitrate is added to the soluble salt solution of the active metal element in Example 6, and the molar ratio of zirconium element to NF is 0.15:1.
[0048] Example 7
[0049] On the basis of Example 1, in order to explore the effect of a single cobalt element on the catalyst, the present invention does not add zirconium nitrate to the soluble salt solution of the active metal element in Example 1, and adjusts the amount of cobalt nitrate added to adjust the molar ratio of cobalt element to NF to within the range of 0.05-0.25:1, thereby forming a comparative experiment.
[0050] Comparative Example 1 is NF after pretreatment.
[0051] Performance Testing
[0052] The catalysts obtained in the embodiments of the present invention and the comparative examples were used to test the catalytic oxidation degradation performance of o-xylene. The test method was to use a continuous flow quartz reactor filled with different catalyst powders to catalytically oxidize o-xylene. A gas chromatograph (GC-2014, Shimadzu, Japan) was used to analyze and detect the concentration of o-xylene in the gas mixture introduced into the reactor before and after catalytic oxidation, and the conversion rate of o-xylene was calculated. Reaction conditions: catalyst filling amount: 1g, o-xylene concentration in the initial gas mixture: 310ppm, space velocity: 10800mL / (gh), gas flow rate: 180mL / min, oxygen concentration: 20%, equilibrium time: 1h. The specific test results are shown in Table 1.
[0053] Table 1
[0054] Test items mark <![CDATA[T 90 (℃)]]> Example 1 <h2 style=";text-align:left;direction:ltr"><![CDATA[Co <h2 style=";text-align:left;direction:ltr"> 0.15 <h2 style=";text-align:left;direction:ltr"> Zr<h2 style=";text-align:left;direction:ltr"> 0.075 <h2 style=";text-align:left;direction:ltr"> -NF]]><h2 style=";text-align:left;direction:ltr"> 203 Example 2 <h2 style=";text-align:left;direction:ltr"><![CDATA[Co <h2 style=";text-align:left;direction:ltr"> 0.15 <h2 style=";text-align:left;direction:ltr"> Zr<h2 style=";text-align:left;direction:ltr"> 0.015 <h2 style=";text-align:left;direction:ltr"> -NF]]><h2 style=";text-align:left;direction:ltr"> 216 Example 3 <h2 style=";text-align:left;direction:ltr"><![CDATA[Co <h2 style=";text-align:left;direction:ltr"> 0.15 <h2 style=";text-align:left;direction:ltr"> Zr<h2 style=";text-align:left;direction:ltr"> 0.0375 <h2 style=";text-align:left;direction:ltr"> -NF]]><h2 style=";text-align:left;direction:ltr"> 211 Example 4 <h2 style=";text-align:left;direction:ltr"><![CDATA[Co <h2 style=";text-align:left;direction:ltr"> 0.15 <h2 style=";text-align:left;direction:ltr"> Zr<h2 style=";text-align:left;direction:ltr"> 0.1125 <h2 style=";text-align:left;direction:ltr"> -NF]]><h2 style=";text-align:left;direction:ltr"> 207 Example 5 <h2 style=";text-align:left;direction:ltr"><![CDATA[Co <h2 style=";text-align:left;direction:ltr"> 0.15 <h2 style=";text-align:left;direction:ltr"> Zr<h2 style=";text-align:left;direction:ltr"> 0.15 <h2 style=";text-align:left;direction:ltr"> -NF]]><h2 style=";text-align:left;direction:ltr"> 210 Example 6 <![CDATA[Co (0.05-0.25) -NF]]> 248-262 Example 7 <![CDATA[Zr 0.15 -NF]]> 265 Comparative Example 1 Pretreatment NF 342
[0055] Based on the above ideal embodiments of the present invention, the relevant staff can make various changes and modifications without departing from the technical concept of the present invention through the above description. The technical scope of the present invention is not limited to the contents of the specification, and its technical scope must be determined according to the scope of the claims.
Claims
1. A method for preparing a CoZr-NF monolithic catalyst for catalytic oxidation of o-xylene, characterized in that: The following steps are involved: NF is placed in a quartz tube, and the quartz tube is heated to 200°C and kept at a constant temperature for 2-3 hours. Then, the quartz tube is heated to 550°C and kept at a constant temperature for 2-3 hours. After the reaction is completed, the CoZr-NF monolithic catalyst is obtained. When the temperature of the quartz tube is raised to 200°C, the carrier gas passes all the reactive aerosol from one end of the quartz tube and is discharged from the other end of the quartz tube. The reactive aerosol is obtained by atomizing a soluble salt solution of an active metal element. The NF is circular in shape, and the diameter of the NF is exactly equal to the inner diameter of the quartz tube. The NF is placed in the quartz tube in a manner of being tangential to the inner wall of the quartz tube to seal the quartz tube.
2. The method for preparing a CoZr-NF monolithic catalyst for catalytic oxidation of o-xylene according to claim 1, characterized in that: The carrier gas is nitrogen or an inert gas.
3. The method for preparing a CoZr-NF monolithic catalyst for catalytic oxidation of o-xylene according to claim 1, characterized in that: The active metal elements include Co and Zr.
4. The method for preparing a CoZr-NF monolithic catalyst for catalytic oxidation of o-xylene according to claim 3, characterized in that: The molar ratio of Zr to Co in the active metal elements is 0.1-1:1, and the molar ratio of Co to NF is 0.05-0.25:
1.
5. A method for preparing a CoZr-NF monolithic catalyst for catalytic oxidation of o-xylene according to any one of claims 1 to 4, characterized in that: The NF is a pretreated NF, and the pretreatment method comprises the following steps: The NF was ultrasonically cleaned with deionized water, hydrochloric acid, and anhydrous ethanol for at least 10 min, and then vacuum dried. Finally, it was calcined at 600 °C for 3 h.
6. The method for preparing a CoZr-NF monolithic catalyst for catalytic oxidation of o-xylene according to claim 5, characterized in that: The concentration of hydrochloric acid is 3-5 mg / mL.
7. The method for preparing a CoZr-NF monolithic catalyst for catalytic oxidation of o-xylene according to claim 1, characterized in that: The average pore size of the NF is 110 PPI.
Citation Information
Patent Citations
Monolithic catalyst with high activity and low cost as well as preparation method and application thereof
CN115608368A